(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Human resources are a very important factor possessed by an agency, organization or company, because their existence is the key that determines the development of an organization. The decline in job satisfaction can be seen from the phenomenon that occurred at the Tirta Amertha Buana Perumda Office, showing a lack of employee job satisfaction as indicated by declining employee performance. The aim of this research is to determine the influence of work discipline, perceived organizational support and career development on job satisfaction. This research used all Perumda employees as a research sample with a total of 182 people. The data collection method uses a questionnaire containing a Likert scale for each indicator statement of the research variable. The analysis technique used is multiple linear regression analysis technique. The results of this research are that partially work discipline, perceived organizational support and career development have a positive and significant effect on job satisfaction. Simultaneously, work discipline, perceived organizational support and career development have a significant effect on job satisfaction of Perumda Tirta Amertha Buana employees, Tabanan Regency. It can be suggested that companies pay attention to work discipline, perceived organizational support and career development because these variables are able to increase employee job satisfaction, which is hoped to be able to improve the performance of Perumda Tirta Amertha Buana, Tabanan Regency